Optimization of conditions for in vitro development of Trichoderma viride-based biofilms as potential inoculants - Triveni, Sodimalla; Prasanna, Radha; Saxena, Anil Kumar (Folia microbiologica, 2012)
Biofilms represent mixed communities present in a diverse range of environments; however, their utility as inoculants is less investigated. Our investigation was aimed towards in vitro development of biofilms using fungal mycelia (Trichoderma viride) as matrices and nitrogen-fixing and P-solubilizing bacteria as partners, as a prelude to their use as biofertilizers (biofilmed biofertilizers, BBs) and biocontrol agents for different crops. The most suitable media in terms of population counts, fresh mass and dry biomass for Trichoderma and Bacillus subtilis/Pseudomonas fluorescens was found to be Pikovskaya broth ± 1 % CaCO(3), while for Trichoderma and Azotobacter chroococcum, Jensen's medium was most optimal. The respective media were then used for optimization of the inoculation rate of the partners in terms of sequence of addition of partners, fresh/dry mass of biofilms and population counts of partners for efficient film formation. Microscopic observations revealed significant differences in the progress of growth of biofilms and dual cultures. In the biofilms, the bacteria were observed growing intermingled within the fungal mycelia mat. Further, biofilm formation was compared under static and shaking conditions and the fresh mass of biofilms was higher in the former. Such biofilms are being further characterized under in vitro conditions, before using them as inoculants with crops.
Keywords: Agricultural Inoculants; očkovadla agrotechnická; biofilmy; Mycelium; kultivační média; mycelium; Biofilms; Trichoderma; Culture Media